The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/dir.20061
|View full text |Cite
|
Sign up to set email alerts
|

Development of a scale to measure the perceived benefits and risks of online shopping

Abstract: n this paper, we report the development of scales to measure the perceived benefits and risks associated with online shopping. Based on an exploratory qualitative inquiry and quantitative assessment, a four-factor scale of perceived benefits and a three-factor scale of perceived risks of online shopping were developed. Results from two national samples support the proposed measures of perceived benefits and risks associated with online shopping in terms of construct, convergent, discriminate, nomological, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
545
2
38

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 680 publications
(671 citation statements)
references
References 77 publications
19
545
2
38
Order By: Relevance
“…This can also cause perceived time risk. Time risks may also include the inconvenience experience that customers face during making online transactions, navigating and submitting orders and delays in getting the products (Forsythe, Liu, Shannon, & Gardner, 2006). Thus the time spent in waiting the transaction to complete consider as time risk also.…”
Section: Perceived Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…This can also cause perceived time risk. Time risks may also include the inconvenience experience that customers face during making online transactions, navigating and submitting orders and delays in getting the products (Forsythe, Liu, Shannon, & Gardner, 2006). Thus the time spent in waiting the transaction to complete consider as time risk also.…”
Section: Perceived Riskmentioning
confidence: 99%
“…They are worried about their pre-purchase experience as they afraid to face the unexpected loss from the purchase and product (Naiyi, 2004). In addition, based on the study done by Forsythe, et al (2006), they found that the perceived benefit significantly affects the consumers' online intention. Perceived benefits are the results that related to the integration, which are valued by every individual.…”
Section: Introductionmentioning
confidence: 99%
“…To measure perceived business benefits, this research adapted applicable constructs from an instrument initially used to measure business benefits emanating from website adoption [14].…”
Section: Scale To Measure Social Capital and Benefits On Snsmentioning
confidence: 99%
“…A recent study by Schibrowsky et al (2007) Specific consumer research foci include, but are not restricted to, consumers' choices among different channels and what drives them to the online channel (Choudhury and Karahanna, 2008;Frambach et al, 2007;Montoya-Weiss and Grewel, 2003;;KaufmanScarborough and Lindquist, 2002;Poel and Leunis, 1999;Shoenbachler and Gorde, 2002;Reibstein, 2002;Alba et al,1997), web characteristics and implications of that on interactions with consumers (Fiore et al, 2005;Hoffman and Novak, 1997;Hoffman and Novak and Chatterjee, 1995;McKenna, 1995;Keeny and Marshall, 2000;Chaffey, 2000); typology of online customers (Kau et al, 2003;Mathwick, 2002), consumer motivations for web use including perceived benefits and risks of online shopping and use of technology (Jose-Cebezudo, 2008;Im et al, 2008;Forsythe, 2006;Joines et al, 2003), consumer search behaviour and purchasing process via the web (Jepsen, 2007;Pavlou and Fygenson, 2006;Rowley, 2000;McGaughey and Manson, 2001;Bruce, 1999), how to attract customers to web sites and how to retain them (Boehm, 2008;Hoffman and Novak, 2000;Parsons et al, 1998;Reibsten, 2002 ), how to reach customer satisfaction and loyalty in the online market (Anderson and Srinivasan, 2003). These studies focused on the impact of internet marketing on consumers and thus aimed to discover how to create business via this new electronic medium and how to regulate the relationship between firms and customers via the web to capitalize on the opportunities created.…”
Section: Consumer Issuesmentioning
confidence: 99%